Effect of Minimum-Volume Standards on Patient Outcomes and Surgical Practice Patterns for Hysterectomy - Ruiz, Maria P. (Obstet Gynecol, 2018)
OBJECTIVE: To model the effect of implementing minimum-volume standards for women who underwent hysterectomy on patient outcomes and surgeon practice patterns. METHODS: We conducted a retrospective cohort study using the New York Statewide Planning and Research Cooperative System (SPARCS) to capture all women who underwent hysterectomy from 2010 to 2014. We estimated the number of hysterectomies performed by each patient’s physician during the prior year. Multivariable models were utilized to estimate the ratio of observed-to-expected (O/E) complications based on each surgeon’s volume during the prior year. The mean O/E ratio of surgeons was then plotted by volume. The number of patients and surgeons that would be eliminated and the reduction in complications if minimum-volume standards (lowest 5(th) and 10(th) percentiles) were implemented were analyzed. Separate analyses were performed for each route of hysterectomy. RESULTS: We identified a total of 127,202 patients. For abdominal hysterectomy, increasing surgeon volume was associated with a decreasing rate of complications (P<0.001). Overall, 17.5% of surgeons (n=1260) had a prior year volume of 1 abdominal hysterectomy. The mean O/E ratio of surgeons with a prior year abdominal hysterectomy volume of 1 was 1.47 (SD=2.71). Within this group of surgeons, 31.4% had an O/E ratio of ≥1 indicating a higher than expected complication rate while 68.7% of the surgeons had a O/E ratio of <1 suggesting a lower complication rate than expected based on case mix. Selection of a prior year volume standard of 1 would restrict 12.5% of surgeons performing robotic-assisted, 16.8% of those performing laparoscopic, and 27.6% of surgeons performing vaginal hysterectomy. CONCLUSION: Implementing minimum-volume standards for hysterectomy, for even the lowest volume physicians, would restrict a significant number of gynecologic surgeons including many with outcomes that are better than predicted.